(untitled) (Perioperaciina Medicina, 2021)
Background. Due to the significant spread of the COVID-19 pandemic and the available contact route of transmission, there is a growing interest in the possibility of using antiseptics to prevent contagion of this viral disease. However, the list of antiseptic drugs for local application is limited. The aim: to investigate the possibility and feasibility of clinical use of decamethoxine as an antiseptic during the infectious COVID-19 pandemic. Materials and methods. Researches and systematic reviews published between 2001 and 2020 were studied using PubMed and Google Scholar searches. Results. It is shown that decamethoxine is an active antiseptic drug, the clinical effectiveness of which has been proven in patients with various pathologies (including bronchial and pulmonary diseases). Decamethoxine can be used in various ways, that provides a variety of routes to deliver the drug to the patient, and it has a strong antiviral activity against different groups of viruses. Conclusions. The analysis demonstrates the feasibility of using decamethoxine solutions to prevent the occurrence and spread of COVID-19 infection.